2022
DOI: 10.1177/03000605221123683
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian pregnancy after bilateral salpingectomy in a patient with in vitro fertilization: a case report

Abstract: Ovarian pregnancy is rare but may occur with in vitro fertilization-embryo transfer in women who have undergone bilateral salpingectomy. We report a case of an approximately 30-year-old woman who had in vitro fertilization and a history of bilateral salpingectomy, and was diagnosed with an ovarian pregnancy. Laparoscopic enucleation of the gestational product in the ovary and ovarian remnant reconstruction were performed. The patient recovered well after surgery and was discharged home 5 days postoperatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…One possible mechanism for the extrauterine implantation of the embryo is the difficulty of ET and even perforation of the uterus during ET. [ 8 ] However, this explanation does not fit this case. ET was applied using a very soft and flexible catheter under direct vision with intensive transabdominal ultrasound guidance, so any perforation would have been seen in real-time, even though the patient had a little trouble during ET.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…One possible mechanism for the extrauterine implantation of the embryo is the difficulty of ET and even perforation of the uterus during ET. [ 8 ] However, this explanation does not fit this case. ET was applied using a very soft and flexible catheter under direct vision with intensive transabdominal ultrasound guidance, so any perforation would have been seen in real-time, even though the patient had a little trouble during ET.…”
Section: Discussionmentioning
confidence: 84%
“…The incidence of HP in all spontaneous pregnancies is less than 1 in 30,000, [2] while the incidence of HP is approximately increasing to a rate of 0.1% to 1% following ART. [1,2,4] Meanwhile, ART also increases the chance of rare implantation sites of EP, such as abdominal pregnancy, [5] interstitial pregnancy, [6] ovarian pregnancy, [7,8] and even intramural pregnancy(IMP). [9] IMP is extremely rare and was first described by Lu et al, [10] accounting for fewer than 1% of total ectopic pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 2022, Zhang et al attributed the presence of a fallopian tube stump alongside a uterine cornual fistula to be the main cause of an ectopic pregnancy post IVF-ET treatment. 15 Another rare case of spontaneous intrauterine pregnancy post bilateral salpingectomy was reported in 2004 by Bollapragada et al which suggested a patent cornual end or a suspected fistulous tract to be the possible cause for the same. 4 Our case is unique in that a 2nd 'spontaneous' ectopic pregnancy has developed at the left uterine cornua despite a bilateral salpingectomy done for previous ectopic pregnancies.…”
Section: Discussionmentioning
confidence: 98%